PENERAPAN MODEL KONVENSIONAL DAN HOUTHAKKER-TAYLOR DALAM MENGANALISIS PERMINTAAN BERAS DI JAWA TIMUR - Asnah Asnah; Dyanasari Dyanasari (BUANA SAINS, 2008)
This research was aimed to recognize determinant factors influencing rice demand behaviour, income elasticity number, its price elasticity, cross price elasticity and rice demand number in East Java which are needed in incoming ten years. This research used secondary time series data during 32 years, starting from 1971 until 2002. The data was processed and analyzed with Houthakker-Taylor dynamic demand behavior analysis and conventional models. In the meantime rice demand projection was predicted by a technique developed by Ferris (1998). Analysis of results showed that the partial factors influencing toward rice demand in East Java were rice price of delta, corn price, corn price of delta, cassava price of delta, flour price of delta, inhabitants’ number of delta, income per capita of delta, and rice demand of lag. Houthakker-Taylor model is better than conventional model used for analyzing rice demand in East Java